International wildlife law : an analysis of international treaties concerned with the conservation of wildlife - Lyster, Simon (Cambridge : Cambridge University Press, 1993)
The Research Center for International Law, University of Cambridge, in association with the International Union for Conservation of Nature and Natural Resources
Keywords: Wildlife conservation -- Law and legislations